HUBUNGAN MOTIVASI DAN IKLIM KERJA DENGAN KINERJA GURU SMP - Farida Elismatuti; Rohiat Rohiat; Turdjai Turdjai (UNIVERSITAS BENGKULU, 2017)
This research was done with the purpose of research find out the relationship between motivation of work with the performance of , knowing the relationship clmate work the performance of teachers, and know the relationship with between motivation to work and the climate working with the performance teacher middle Junior High Land In Distrit STL Ulu Terawas. There were 37 the teachers as a samples of the commencement of research. Analysis of used in this research is a correlation double and regression double. The results of this research shows that (1) there was a positive correlation between motivation (X1) with performance (Y); (2) there was a positive correlation between climate work (X2) with performance (Y); (3) there was a positive correlation between motivation and climate work (X1,2) with performance (Y) of the state teachers junior the district STL Ulu Terawas.